2021
DOI: 10.1001/jamasurg.2021.2380
|View full text |Cite|
|
Sign up to set email alerts
|

Characteristics of Early-Onset vs Late-Onset Colorectal Cancer

Abstract: Table. Pathological Features and Molecular Profile of Early-Onset Colorectal Cancer Pathological features Molecular profile Poor differentiation Microsatellite stability Mucinous tumors More likely to exhibit LINE-1 hypomethylation and TP53 sequence variations Signet-ring morphology Less frequently harbor KRAS, BRAF V600E, and APC sequence variations Perineural/venous invasion Promoter methylation of CpG islands Abbreviations: APC, adenomatous polyposis coli; BRAF, B-Raf; KRAS, K-Ras; LINE-1, long interspersed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(82 citation statements)
references
References 74 publications
1
66
0
Order By: Relevance
“…Colorectal cancer is the frequent cancer globally and has high mortality and incidence rates ( Wieszczy et al, 2020 ; Świerczyński et al, 2021 ; Zaborowski et al, 2021 ; Zhao et al, 2021 ). Bi et al (2020) revealed that LINC01116 was highly expressed in CRC tissues compared to normal tissues, and patients with high expression of LINC01116 had a very poor prognosis.…”
Section: Expression and Clinical Characteristics Of Linc01116 In Various Cancer Typesmentioning
confidence: 99%
“…Colorectal cancer is the frequent cancer globally and has high mortality and incidence rates ( Wieszczy et al, 2020 ; Świerczyński et al, 2021 ; Zaborowski et al, 2021 ; Zhao et al, 2021 ). Bi et al (2020) revealed that LINC01116 was highly expressed in CRC tissues compared to normal tissues, and patients with high expression of LINC01116 had a very poor prognosis.…”
Section: Expression and Clinical Characteristics Of Linc01116 In Various Cancer Typesmentioning
confidence: 99%
“…Combined efforts in the field of colorectal cancer (CRC) have tremendously advanced the understanding, prognosis and treatment of this deadly disease over the past decades. Main contributors for the overall improved outcome are preventive screening strategies for early detection, as colonoscopy, stool (DNA) analysis and therapeutic options through blood-based biomarkers, personalized treatments and immunotherapy [ 1 , 2 , 3 ]. Though, as of today, alarming and devastating global patterns are being recognized and show themselves in the extensively increasing number of incidences especially in young adults over the past 25 years, ranking CRC still as third (US) and fourth worldwide deadliest cancer entity [ 2 , 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Main contributors for the overall improved outcome are preventive screening strategies for early detection, as colonoscopy, stool (DNA) analysis and therapeutic options through blood-based biomarkers, personalized treatments and immunotherapy [ 1 , 2 , 3 ]. Though, as of today, alarming and devastating global patterns are being recognized and show themselves in the extensively increasing number of incidences especially in young adults over the past 25 years, ranking CRC still as third (US) and fourth worldwide deadliest cancer entity [ 2 , 4 , 5 , 6 , 7 , 8 ]. The mortality, morbidity and early onset of CRC are expected to increase even further and main contributors to this development are not entirely understood, though hypothesized to root in changed lifestyle habits, such as smoking, diet, alcohol and obesity [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…As described, there is compelling evidence that EOCRC and LOCRC are distinct entities [ 38 ], varying regarding genetic predisposition, location, histopathology, molecular classification and the presence of more advanced disease and poorer outcome for EOCRC. As opposed to LOCRC, younger patients frequently present with disease in the distal colon and rectum with multiple lesions and unfavorable histology [ 45 ]. The poorer outcome in EOCRC is in part due to the absence, until recently, of a risk-based screening and surveillance strategy for those individuals younger than 50 years of age.…”
Section: Introductionmentioning
confidence: 99%